Rubber composition for fender and fender

A rubber composition with natural rubber, butadiene rubber, and carbon black, without aromatic oils and amine anti-aging agents, addresses adhesion and aging issues in fenders, ensuring durable and aesthetically pleasing performance.

JP7617391B2Active Publication Date: 2025-01-20THE YOKOHAMA RUBBER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021013312
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-29
Publication Date
2025-01-20
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

Conventional rubber compositions for fenders exhibit poor adhesion to iron, heat aging resistance, and stain resistance, particularly when containing natural rubber and styrene-butadiene rubber, silica, or aromatic oils and amine anti-aging agents.

Method used

A rubber composition comprising natural rubber, butadiene rubber, and carbon black, with specific content ranges and absence of aromatic oils and amine anti-aging agents, along with a plasticizer like paraffin oil, enhances adhesion to iron and provides heat aging resistance and stain resistance.

Benefits of technology

The composition achieves excellent adhesion to iron, superior heat aging resistance, and improved stain resistance, maintaining aesthetic appearance over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617391000005
    Figure 0007617391000005
  • Figure 0007617391000006
    Figure 0007617391000006
  • Figure 0007617391000001
    Figure 0007617391000001
Patent Text Reader

Abstract

To provide a rubber composition for fenders that is excellent in adhesion to iron, thermal aging resistance and stain resistance, and provide a fender.SOLUTION: A rubber composition for fenders contains a rubber component containing natural rubber and butadiene rubber, and carbon black. A content of butadiene rubber is 40 mass% or less in a total amount of the rubber component, a total content of natural rubber and butadiene rubber 90 mass% or more in the total amount of the rubber component, and a content of carbon black is 30-60 pts.mass relative to 100 pts.mass of the rubber component. The rubber composition for fenders is substantially free of an aroma oil with CA% of 25% or more, obtained by composition analysis by the Kurtz method, and is also substantially free of an amine age resister. There is also provided a fender formed using the rubber composition for fenders.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition for a fender and a fender. [Background technology]

[0002] Conventionally, fenders have been used to absorb the energy generated when a ship comes alongside a berthing vessel. Usually, fenders are made of rubber and have a cavity, to which metal fittings for connecting air valves, etc. are attached. In most cases, the metal fittings are made of steel.

[0003] On the other hand, various rubber compositions have been proposed as rubber compositions for fenders (for example, Patent Documents 1 and 2). Patent Document 1 describes a rubber composition for a fender that contains 25 to 35 parts by mass of silica and a silane coupling agent per 100 parts by mass of rubber containing 20 to 50% by mass of butadiene rubber, for the purpose of providing a fender that has excellent abrasion resistance and weather resistance, and a rubber composition for a fender that has excellent abrasion resistance and weather resistance. Patent Document 2 describes a rubber composition for a fender cover layer, which contains 100 parts by mass of rubber including natural rubber and styrene butadiene rubber in a mass ratio of 70 / 30 to 30 / 70, 40 to 60 parts by mass of carbon black, 0.5 to 3.0 parts by mass of sulfur, and 0.5 to 1.5 parts by mass of dibenzothiazyl disulfide, and the compounding ratio of the sulfur to the dibenzothiazyl disulfide (sulfur / dibenzothiazyl disulfide) is 1.1 to 3.0, for the purpose of providing a rubber composition for a fender cover layer that has excellent abrasion resistance and tear resistance and high tensile strength and elongation (elongation at break). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-179656 A [Patent Document 2] JP 2013-194155 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present inventors prepared and evaluated rubber compositions with reference to Patent Documents 1 and 2, and found that when a rubber composition contains natural rubber and styrene-butadiene rubber as rubber components, the adhesiveness and / or heat aging resistance of a cured product of the rubber composition to iron fittings may be poor. It was also revealed that when the material contained only natural rubber and styrene-butadiene rubber, adhesion to iron fittings was sometimes poor. It has become apparent that when a rubber composition contains silica, the adhesion between a cured product of the rubber composition and iron fittings may be poor.

[0006] In general, the rubber composition may further contain a plasticizer and an antioxidant for the purposes of plasticizing the rubber and preventing aging. Examples of the plasticizer include petroleum-based softeners and plant-derived plasticizers. Petroleum-based softeners usually refer to softeners (plasticizers) derived from crude oil, and examples of the petroleum-based softeners include process oils and extender oils. The petroleum-based softeners are classified into paraffinic, naphthenic, and aromatic softeners based on their composition. For classification of petroleum-based softeners into aromatic softeners based on their composition, see "Petroleum-Based Softeners" in Journal of the Society of Rubber Science and Technology, Vol. 50, No. 10, 1977, pp. 664-671. However, it has become clear that when a rubber composition containing an aromatic oil or an amine-based antioxidant is used to form a fender, the fender may be discolored.

[0007] Therefore, an object of the present invention is to provide a rubber composition for a fender which has excellent adhesion to iron, heat aging resistance and stain resistance. Another object of the present invention is to provide a fender. [Means for solving the problem]

[0008] As a result of intensive research into solving the above problems, the present inventors have found that the desired effects can be obtained by a rubber composition containing a rubber component including natural rubber and butadiene rubber, and carbon black, wherein the content of butadiene rubber, the total content of natural rubber and butadiene rubber, and the content of carbon black are within specific ranges, and the rubber composition is substantially free of specific aromatic oils or amine-based anti-aging agents, thereby completing the present invention. The present invention is based on the above findings and has the following specific configuration to solve the above problems.

[0009] [1] A rubber component including natural rubber and butadiene rubber, and carbon black, the content of the butadiene rubber is 40% by mass or less based on the total amount of the rubber component, a total content of the natural rubber and the butadiene rubber is 90% by mass or more of a total amount of the rubber component, The content of the carbon black is 30 to 60 parts by mass based on 100 parts by mass of the rubber component, C obtained by composition analysis using the Kurtz method A Contains substantially no aromatic oil with a content of 25% or more; A rubber composition for a fender, which is substantially free of an amine-based antioxidant. [2] The rubber composition for a fender according to [1], further comprising a plasticizer (excluding the aromatic oil), the plasticizer including paraffin oil. [3] The rubber composition for a fender according to [2], wherein the content of the plasticizer is 5 to 20 parts by mass per 100 parts by mass of the rubber component. [4] The rubber composition for a fender according to any one of [1] to [3], wherein the amount of the carbon black is 40 to 59 parts by mass per 100 parts by mass of the rubber component. [5] The rubber composition for a fender according to any one of [1] to [4], wherein the rubber component does not substantially contain styrene-butadiene rubber. [6] The rubber composition for a fender according to any one of [1] to [5], wherein the rubber component contains only natural rubber and butadiene rubber. [7] It also contains sulfur. The rubber composition for a fender according to any one of [1] to [6], wherein the amount of the sulfur is 1.7 to 2.2 parts by mass per 100 parts by mass of the rubber component. [8] The rubber composition for a fender according to any one of [1] to [7], further comprising a vulcanization accelerator, the vulcanization accelerator including a thiazole-based vulcanization accelerator. [9] A fender formed using the rubber composition for a fender according to any one of [1] to [8].

[10] An outer layer and an inner layer, and optionally a reinforcing layer between the outer layer and the inner layer, the reinforcing layer having a reinforcing material and a coating layer; The fender according to [9], wherein either or both of the inner layer and the coating layer are each independently formed using the rubber composition for a fender.

[11] A fender as described in [9] or

[10] , the exterior color of which is white or colored. Effect of the Invention

[0010] The rubber composition for a fender of the present invention is excellent in adhesion to iron, heat aging resistance and stain resistance. Furthermore, the fender of the present invention has excellent adhesion to iron, heat aging resistance and stain resistance. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view that illustrates an example of a fender of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that shows a schematic diagram of A which is a part of the main body 102 shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In this specification, unless otherwise specified, each component may be used alone or in combination of two or more substances corresponding to that component. When a component contains two or more substances, the content of the component means the total content of the two or more substances. In this specification, the rubber composition for a fender of the present invention or the fender of the present invention may be said to have better effects in that at least one of adhesion to iron, heat aging resistance, and stain resistance is better.

[0013] [Rubber composition for fenders] The rubber composition for a fender of the present invention (rubber composition of the present invention) is The rubber component contains natural rubber and butadiene rubber, and carbon black, the content of the butadiene rubber is 40% by mass or less based on the total amount of the rubber component, a total content of the natural rubber and the butadiene rubber is 90% by mass or more of a total amount of the rubber component, The content of the carbon black is 30 to 60 parts by mass based on 100 parts by mass of the rubber component, C obtained by composition analysis using the Kurtz method A Contains substantially no aromatic oil with a content of 25% or more; The rubber composition for a fender contains substantially no amine-based antioxidant. Each component contained in the rubber composition of the present invention will be described in detail below.

[0014] <<Rubber component>> In the present invention, the rubber component includes natural rubber and butadiene rubber.

[0015] <Natural rubber> In the present invention, the natural rubber contained as the rubber component is not particularly limited, and examples thereof include conventionally known natural rubbers.

[0016] <Butadiene rubber> In the present invention, the butadiene rubber contained as the rubber component is not particularly limited. For example, a conventionally known butadiene rubber may be used. Note that the butadiene rubber does not include styrene-butadiene rubber.

[0017] (Other rubber) The rubber component may further contain rubbers other than natural rubber and butadiene rubber (other rubbers). Examples of other rubbers include diene rubbers such as polyisoprene rubber (IR), butyl rubber (IIR), acrylonitrile butadiene rubber (NBR), and chloroprene rubber (CR); ethylene propylene copolymer rubber, chlorosulfonated polyethylene, acrylic rubber, epichlorohydrin rubber, and silicone rubber.

[0018] <Butadiene rubber content> In the present invention, the content of the butadiene rubber is 40% by mass or less based on the total amount of the rubber component. Note that, in the present invention, the content of the butadiene rubber is more than 0% by mass based on the total amount of the rubber component. By having the butadiene rubber content in the above range, the rubber composition of the present invention has excellent heat aging resistance and adhesion to iron.

[0019] The content of the butadiene rubber is preferably 25 to 35 mass % and more preferably 28 to 35 mass % of the total amount of the rubber component, from the viewpoints of obtaining better effects of the present invention and excellent storage stability.

[0020] (Natural rubber content) In the present invention, the content of natural rubber may be 60% by mass or more and less than 100% by mass of the total amount of the rubber component. When the content of natural rubber is within the above range, the rubber composition of the present invention has excellent heat aging resistance, storage stability, and tensile strength.

[0021] The content of the natural rubber is preferably 65 to 75 mass %, and more preferably 65 to 72 mass %, of the total amount of the rubber component, from the viewpoints of achieving better effects of the present invention and excellent storage stability.

[0022] <Total content of natural rubber and butadiene rubber> In the present invention, the total content of the natural rubber and the butadiene rubber is 90% by mass or more based on the total amount of the rubber component. When the total content is within the above range, the rubber composition of the present invention has excellent heat aging resistance and adhesion to iron.

[0023] From the viewpoint of obtaining superior effects of the present invention, the total content is preferably from 95 to 100% by mass, and more preferably 100% by mass, based on the total amount of the rubber component.

[0024] Styrene butadiene rubber From the viewpoint of obtaining better effects of the present invention (particularly, better adhesion to iron and better resistance to heat aging), it is preferable that the rubber component does not substantially contain styrene-butadiene rubber (SBR). The styrene-butadiene rubber is not particularly limited as long as it is a copolymer of styrene and butadiene. In the present invention, "the rubber component does not substantially contain styrene-butadiene rubber" means that the amount of styrene-butadiene rubber in the total amount of the rubber component is 0 to 1.0% by mass.

[0025] Natural rubber and butadiene rubber only From the viewpoint of obtaining better effects of the present invention (particularly better adhesion to iron), the rubber component preferably contains only natural rubber and butadiene rubber.

[0026] <<Carbon black>> The rubber composition of the present invention contains carbon black. The carbon black is not particularly limited, and examples of the carbon black include FEF (Fast Extruding Furnace) grade, GPF (General Purpose Furnace) grade, and SRF (Semi-Reinforcing Furnace) grade carbon black.

[0027] From the viewpoint of obtaining a more excellent effect of the present invention, the carbon black is preferably one having a nitrogen adsorption specific surface area (N2SA) of 20 to 50 m 2 / g, and the nitrogen adsorption specific surface area (N2SA) is 25 to 30 m 2 It is more preferred that the carbon black comprises 0.1 wt. / g. The nitrogen adsorption specific surface area of ​​carbon black can be measured in accordance with JIS K6217-2:2017. From the viewpoint of obtaining a more excellent effect of the present invention, the carbon black preferably contains GPF-class carbon black. Commercially available GPF grade carbon black products include, for example, DASHBLACK (manufactured by OCI) and Niteron #GN (manufactured by Nippon Steel Carbon Corporation).

[0028] <Carbon black content> In the present invention, the content of carbon black is 30 to 60 parts by mass per 100 parts by mass of the rubber component. By having the carbon black content in the above range, the rubber composition of the present invention has excellent heat aging resistance, and an excellent balance between the heat aging resistance and the hardness of the cured product of the rubber composition of the present invention.

[0029] The amount of carbon black is preferably from 40 to 59 parts by mass, and more preferably from 45 to 55 parts by mass, per 100 parts by mass of the rubber component, from the viewpoint of achieving superior effects of the present invention.

[0030] ((Aroma oil)) The rubber composition of the present invention has a C A The aromatic oil composition is essentially free of aromatic oils having a C content of 25% or more. A Aroma oils with a % of 25% or more are sometimes referred to as "specific aroma oils." The rubber composition of the present invention is excellent in contamination resistance because it is substantially free of the specific aromatic oil. Furthermore, even if the rubber composition adjacent to the rubber composition of the present invention is white or colored, the adjacent rubber composition is unlikely to be discolored, and the contamination resistance is excellent.

[0031] (C A %) In the present invention, C A % are the VGC (viscosity specific gravity constant) and r measured according to the Kurtz method in accordance with ASTM D2140-08 (2017). i The aromatic ratio is the percentage of aromatic carbon atoms relative to the total carbon number, calculated from the refractive index. (C p %, C N %) In the present invention, C p % are the VGC (viscosity specific gravity constant) and r measured according to the Kurtz method in accordance with ASTM D2140-08 (2017). i The value is derived from the refractive index (paraffin carbon number as a percentage of the total carbon number: paraffin ratio). In the present invention, C N % are the VGC (viscosity specific gravity constant) and r measured according to the Kurtz method in accordance with ASTM D2140-08 (2017). i The naphthene ratio is the percentage of naphthene carbon number to the total carbon number (the refractive index).

[0032] (Aroma oil) Generally, 35% or more C A Aromatic oils are softeners that contain 100% of the aromatic compounds. A There are also aromatic oils with lower percentages than the above values. In the present invention, the C A % shall be 25% or more.

[0033] <Specific aroma oil> In the present invention, the specific aromatic oil has a viscosity specific gravity constant (VGC) and a viscosity specific gravity constant (r) measured according to the Kurtz method in accordance with ASTM D2140-08 (2017). i (Refractive index) derived from C A This refers to petroleum-based softeners with a content of 25% or more. In the present invention, the specific aromatic oil is a 25% or more C A %. An example of a commercially available specific aroma oil is Diana Process AH-20 (manufactured by Idemitsu Kosan Co., Ltd.). In the present invention, "substantially free of specific aroma oil" means that the amount of the specific aroma oil is 0 to 1.0% by mass based on the total amount of the rubber composition of the present invention.

[0034] <Amine-based antioxidant> The rubber composition of the present invention does not substantially contain an amine-based antiaging agent. The rubber composition of the present invention has excellent stain resistance because it does not substantially contain an amine-based antiaging agent. In addition, even if a rubber composition adjacent to the rubber composition of the present invention is white or colored, the adjacent rubber composition is unlikely to be discolored, and the stain resistance is excellent. In the present invention, the amine-based antioxidant refers to a compound having an amino group (-NH2, -NH-) and having the function of preventing rubber aging. Examples of amine-based antioxidants include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6C) and 2,2,4-trimethyl-1,2-dihydroquinoline polymers. In the present invention, "substantially free of amine-based antioxidants" means that the amount of amine-based antioxidants is 0 to 1.0% by mass based on the total amount of the rubber composition of the present invention.

[0035] (Plasticizer) The rubber composition of the present invention preferably further contains a plasticizer, for the reasons that the effects of the present invention (particularly contamination resistance) are more excellent, storage stability is excellent, and deterioration of the physical properties of the cured product after long-term storage can be prevented. However, the plasticizer does not include the above-mentioned specific aromatic oil. Examples of the plasticizer include petroleum-based softeners such as paraffin oil and naphthenic oil (excluding the above-mentioned specific aromatic oils); and plant-derived plasticizers such as castor oil. For the same reasons as above, the above plasticizers should contain less than 25% C. A %, and more preferably paraffin oil.

[0036] Paraffin oil Paraffin oils are characterized by their VGC (viscosity specific gravity constant) and r (viscosity specific gravity constant) measured according to the Kurtz method and in accordance with ASTM D2140-08 (2017). i (Refractive index) derived from C p % is 55% or more. In this specification, paraffin oil does not include the above-mentioned specific aromatic oils.

[0037] Paraffin oil C p The content is more preferably 55 to 75%. Paraffin oil C A % is preferably less than 25%, more preferably 0 to 15%. Paraffin oil C N % is preferably 40% or less, and more preferably 20 to 40%.

[0038] Examples of commercially available paraffin oils include: Showa Shell Machine Oil (C A %4.5%, C P %65%, C N %30.5%), SUNPAR 2280 (C) manufactured by Nippon San Oil A %4.5%, C P %65%, C N%30.5%), Idemitsu Kosan Diana Process Oil PA-32 (C A 3%, C P 70%, C N 27%) are cited.

[0039] Naphthenic oil Naphthenic oils are measured according to the Kurtz method in accordance with ASTM D2140-08(2017) for VGC (viscosity specific gravity constant) and r i (Refractive index) derived from C N % is 20% or more. As used herein, naphthenic oils do not include the specific aromatic oils listed above or the paraffinic oils listed above.

[0040] Naphthenic oil C A % is preferably less than 25%, and more preferably 10% or more and less than 25%. Naphthenic oil C p % is preferably less than 55%, and more preferably 25% or more and less than 55%. Naphthenic oil C N % is preferably 20% or more, and more preferably 40 to 45%.

[0041] (Plasticizer content) The content of the plasticizer is preferably 5 to 20 parts by mass, and more preferably 8 to 15 parts by mass, per 100 parts by mass of the rubber component, because this provides better effects of the present invention (particularly contamination resistance), better storage stability, and prevents deterioration in the physical properties of the cured product after long-term storage.

[0042] (sulfur) From the viewpoint of obtaining superior effects of the present invention (particularly heat aging resistance), the rubber composition of the present invention preferably further contains sulfur. There are no particular limitations on the sulfur.

[0043] (Sulfur content) The content of sulfur is preferably 1.7 to 2.2 parts by mass per 100 parts by mass of the rubber component, from the viewpoint of obtaining superior effects of the present invention (particularly heat aging resistance).

[0044] (Vulcanization accelerator) From the viewpoint of obtaining a better effect of the present invention (particularly adhesion to iron), the rubber composition of the present invention preferably further contains a vulcanization accelerator. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators, sulfenamide-based vulcanization accelerators, dithiocarbamate-based vulcanization accelerators, and thiuram-based vulcanization accelerators. Among them, from the viewpoint of obtaining a better effect of the present invention (particularly adhesion to iron) and being less susceptible to scorching, it is preferable that the vulcanization accelerator contains a thiazole-based vulcanization accelerator. The vulcanization accelerator may have a nitrogen atom.

[0045] The thiazole vulcanization accelerator is not particularly limited as long as it is a compound having a thiazole skeleton, and examples thereof include 2-mercaptobenzothiazole, dibenzothiazolyl disulfide, sodium salt, zinc salt, copper salt, and cyclohexylamine salt of 2-mercaptobenzothiazole, 2-(2,4-dinitrophenyl)mercaptobenzothiazole, and 2-(2,6-diethyl-4-morpholinothio)benzothiazole. From the viewpoint of obtaining superior effects of the present invention (particularly adhesion to iron), the vulcanization accelerator preferably contains dibenzothiazolyl disulfide.

[0046] (Vulcanization accelerator content) The content of the vulcanization accelerator is preferably 0.5 to 5 parts by mass per 100 parts by mass of the rubber component, from the viewpoint of obtaining superior effects of the present invention (particularly adhesion to iron).

[0047] (Additives) The rubber composition of the present invention may further contain additives, if necessary. Examples of the additives include zinc oxide, stearic acid, antioxidants other than amine-based antioxidants, vulcanization retarders, tackifiers, and fillers other than carbon black. The type and content of each of the above additives can be appropriately selected.

[0048] Antioxidants other than amine-based antioxidants Examples of antiaging agents other than amine-based antiaging agents include monophenol-based antiaging agents such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis-, tris-, and polyphenol-based antiaging agents such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. The amount of the antioxidant other than the amine-based antioxidant may be, for example, 0 to 5 parts by mass per 100 parts by mass of the rubber component.

[0049] (Manufacturing method) The method for producing the rubber composition of the present invention is not particularly limited. For example, first, components other than the vulcanizing agent and vulcanization accelerator, such as natural rubber, butadiene rubber, carbon black, and paraffin oil that may be further contained, are mixed under the condition of 100 to 140°C, and the vulcanizing agent and vulcanization accelerator are added to the above mixture and further mixed under the condition of 80 to 100°C, whereby the rubber composition of the present invention can be produced.

[0050] (Vulcanization) The vulcanization conditions for the rubber composition of the present invention are not particularly limited, and may be, for example, at 120 to 150° C. and a pressure of 0.5 to 4 MPa.

[0051] (Application) The rubber composition of the present invention can be used as a rubber composition for a fender.

[0052] [Fender] The fender of the present invention is a fender formed using the rubber composition for fenders of the present invention.

[0053] The type of the fender of the present invention is not particularly limited. Examples of the fender of the present invention include a pneumatic fender and a solid fender.

[0054] (exterior) The fender of the present invention is not particularly limited with respect to its appearance. For example, the color of the exterior of the fender of the present invention is preferably white or colored from the viewpoint of aesthetics. The color is not particularly limited. However, black is excluded from the colors. Examples of the colors include gray, yellow, and orange.

[0055] (Composition: inner layer, outer layer, reinforcing layer) The fender of the present invention is not particularly limited in terms of its configuration. For example, the fender (main body) may be composed of a two-layer laminate (i.e., the fender has an inner layer and an outer layer) or may be composed of a three or more layer laminate. When the fender (main body) is composed of a laminate of three or more layers, for example, the fender may be a fender having an inner layer, an outer layer, and a reinforcing layer. The reinforcing layer is preferably located between the inner layer and the outer layer.

[0056] (Inner layer) The inner layer may be a single layer or multiple layers, as may the outer layer and the reinforcing layer.

[0057] (Reinforcing layer: Reinforcing material and coating layer) The reinforcing layer that the fender of the present invention may optionally have may have, for example, a reinforcing material and a coating layer. Examples of reinforcing materials include fibers such as aramid fibers, glass fibers, nylon fibers, and polyester fibers; and metal cords. In the reinforcing layer, the coating layer preferably covers the reinforcing material.

[0058] <Rubber composition> The rubber composition for a fender used in the fender of the present invention is not particularly limited as long as it is the rubber composition for a fender of the present invention. In addition, there is no particular limitation as to which component part of the fender the rubber composition of the present invention is applied to. For example, the rubber composition of the present invention can be applied to at least one of the inner layer, the outer layer, and the reinforcing layer that the fender may optionally have. When the inner layer has a plurality of layers and the inner layer is formed of the rubber composition of the present invention, any one of the plurality of layers in the inner layer may be formed of the rubber composition of the present invention. In the above case, from the viewpoint of more excellent effects of the present invention, it is preferable that at least the innermost layer is formed of the rubber composition for fender of the present invention. In the reinforcing layer, the rubber composition of the present invention can be applied to, for example, a coating layer. In particular, since the rubber composition of the present invention has excellent adhesion to iron, heat aging resistance, and contamination resistance, it is preferable to apply the rubber composition of the present invention independently to the inner layer of the fender and / or the reinforcing layer that the fender may optionally have (or a coating layer that the reinforcing layer has; the same applies below), and it is more preferable to apply the rubber composition of the present invention independently to the inner layer and reinforcing layer of the fender.

[0059] From the viewpoint of achieving superior effects of the present invention, it is preferable that the fender of the present invention has an outer layer and an inner layer, and optionally has a reinforcing layer between the outer layer and the inner layer, and that either one or both of the inner layer and the reinforcing layer (or the above-mentioned coating layer) are each independently formed using the rubber composition of the present invention, It is more preferable that the tire has an outer layer and an inner layer, and a reinforcing layer is provided between the outer layer and the inner layer, and that both the inner layer and the reinforcing layer (or the above-mentioned coating layer) are each independently formed using the rubber composition of the present invention.

[0060] (outer layer) The material that can constitute the outer layer of the fender of the present invention is preferably a rubber composition from the viewpoint of durability, etc. Examples of rubber compositions that can constitute the outer layer include conventionally known ones. The color of the material that can constitute the outer layer is not particularly limited. The color of the outer layer can be the external color of the fender of the present invention. The method for adjusting the external color (color of the outer layer) of the fender of the present invention is not particularly limited. For example, a conventionally known method can be used.

[0061] The fender of the present invention will be described below with reference to the accompanying drawings, in which: The present invention is not limited to the accompanying drawings. Fig. 1 is a cross-sectional view showing a schematic diagram of an example of the fender of the present invention. The fender shown in Fig. 1 is generally called a pneumatic fender. In FIG. 1, a fender 100 has a main body 102 and metal fittings 104 and 106. The metal fittings 104 and 106 may have, for example, an air valve, a safety valve, and a hanging attachment portion. The metal fittings may be made of, for example, iron. The interior of the fender 100 is filled with, for example, a gas such as air or a liquid, and the fender 100 has elasticity.

[0062] FIG. 2 is a cross-sectional view that shows a schematic diagram of A which is a part of the main body 102 shown in FIG. 2, the main body 102 has an outer layer 200, an inner layer 202, and a reinforcing layer 204. The outer layer 200, the reinforcing layer 204, and the inner layer 202 are laminated in this order. The reinforcing layer 204 is bonded to the outer layer 200 and the inner layer 202. In the present invention, the main body 102 does not necessarily need to have the reinforcing layer 204. In this case, the outer layer 200 and the inner layer 202 are laminated in this order and bonded together. The color of the outer layer 200 is preferably white or colored. There is no particular limitation on the material applied to the outer layer. For example, a rubber composition that can be cured into a white or colored product can be used. The color of the inner layer 202 is not particularly limited, and may be black. The same applies to the reinforcing layer 204. The material applied to the inner layer and / or reinforcing layer (or coating layer) is preferably the rubber composition of the present invention.

[0063] In general, in a certain product, when a first rubber layer (outer layer) that exhibits the above-mentioned product's appearance is adjacent to a second rubber layer (inner layer) made of a rubber composition containing the above-mentioned specific aromatic oil or amine-based antioxidant, discoloration of the first rubber layer may be clearly noticeable. This is thought to be because the specific aromatic oil or amine-based antioxidant migrates from the second rubber layer to the first rubber layer, contaminating the first rubber layer and causing discoloration of the first rubber layer. In the fender of the present invention, for example, the color of the outer layer is white or colored, and the inner layer and / or the optional reinforcing layer are composed of the rubber composition of the present invention, and even if the outer layer and the inner layer are adjacent to each other or the outer layer is laminated to the inner layer via the reinforcing layer, the rubber composition of the present invention constituting the inner layer and / or the reinforcing layer does not substantially contain the specific aroma oil and the amine-based antioxidant, so that the specific aroma oil and the amine-based antioxidant do not migrate from the inner layer and / or the reinforcing layer to the outer layer. Therefore, the fender of the present invention does not discolor its outer layer due to migration (contamination) of the specific aroma oil and the amine-based antioxidant, and has excellent long-term aesthetics. In FIG. 2 , for example, when the color of the outer layer 200 is white or colored and the inner layer 202 and / or the reinforcing layer 204 are made of the rubber composition of the present invention, the specific aroma oil and the amine-based antioxidant will not migrate from the inner layer 202 and / or the reinforcing layer 204 to the outer layer 200, and the outer layer 200 will not be discolored due to the migration, resulting in excellent long-term aesthetics.

[0064] (Manufacturing method) The fender of the present invention is not particularly limited in its production. For example, a conventionally known fender may be used. Specifically, for example, a rubber composition for an outer layer and a rubber composition for an inner layer are laminated (if a reinforcing layer is provided, the reinforcing layer is disposed between the rubber composition for the outer layer and the rubber composition for the inner layer), and the laminate is vulcanized to produce the fender (main body). The vulcanization conditions can be appropriately selected depending on the compounding composition of the rubber composition for the fender. For example, the vulcanization can be performed under conditions of a temperature of 120 to 150° C. and a pressure of 0.5 to 4 MPa. The vulcanization time can be, for example, about 30 to 120 minutes.

[0065] (Metal fittings) The fender (main body) obtained after vulcanization may further have metal fittings. The metal fittings include, for example, iron fittings. The iron fittings may be any metal fittings that contain iron. Specific examples of the metal fittings include air valves, safety valves, and hanging fixture attachment parts. When attaching the metal fittings to the fender (main body) obtained after vulcanization, an adhesive composition (cement) may be used. Examples of the adhesive composition (cement) include a composition containing a phenolic resin. When using the adhesive composition, a primer may be applied to the metal fittings in advance. There are no particular limitations on the primer. Examples include those that are conventionally known. EXAMPLES

[0066] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these.

[0067] <<Production of Rubber Composition>> Each rubber composition was produced by mixing the components in the composition (parts by mass) shown in Table 1 below with a stirrer.

[0068] <<Vulcanization of rubber composition>> Each of the rubber compositions produced as described above was press-vulcanized in a 15×15×0.2 cm mold at 150° C. for 30 minutes to obtain a sheet-like initially vulcanized rubber (thickness: 2 mm).

[0069] <<Evaluation>> The initially vulcanized rubbers thus obtained were subjected to the following evaluations, the results of which are shown in Table 1. <Staining> A migration staining test (accelerated heating method) was carried out visually in accordance with JIS K6267:2006. If the stained material after the test did not change color compared to before the test, this was indicated as "none" and the stain resistance was evaluated as excellent. On the other hand, when the stained material was discolored after the test, it was indicated as "yes" and the stain resistance was evaluated as poor.

[0070] <Heat aging resistance (without storage of rubber composition)> (Sample preparation) From each initial vulcanized rubber obtained as described above, initial test pieces in the shape of dumbbell No. 3 were punched out. (Heat aging test) Each of the initial test pieces punched out as described above was subjected to a heat aging test at 70° C. for 96 hours to obtain test pieces after heat aging.

[0071] (Evaluation method) Using each of the initial test pieces and each of the heat-aged test pieces obtained as described above, a tensile test was performed in accordance with JIS K6251:2010 under conditions of 25°C and a tensile speed of 500 mm / min, to measure the tensile strength (initial TB) [MPa] and elongation at break (initial EB) [%] of each of the initial test pieces, and the (post-heat-aged TB) [MPa] and elongation at break (post-heat-aged EB) [%] of each of the heat-aged test pieces. The tensile strength of each initial test piece obtained as described above is shown in the last column of Table 1 as "Initial TB [MPa]".

[0072] The initial TB and the TB after heat aging obtained as described above were applied to the following formula to calculate the TB retention rate (%). TB retention rate (%) = TB after heat aging / initial TB × 100 The initial EB values ​​and the EB values ​​after heat aging obtained as described above were applied to the following formula to calculate the EB retention rate (%). EB retention rate (%) = EB after heat aging / initial EB × 100

[0073] In the present invention, the "heat aging resistance" is evaluated based on the above-mentioned <Heat aging resistance (without storage of rubber composition)>.

[0074] (Evaluation criteria for heat aging resistance) In the present invention, when the TB and EB retention rates were both 90% or more, the heat aging resistance was evaluated as excellent, and this was indicated by "◯". On the other hand, when at least either the TB or EB retention rate was less than 90%, the heat aging resistance was evaluated as poor, and this was indicated by "X". The greater the retention of TB and / or EB is above 90%, the better the heat aging resistance is.

[0075] <Adhesion to iron (rubber-iron adhesion)> (Sample Preparation) First, cement (product names Metalock P and Metalock G-25, manufactured by Toyo Kagaku Kenkyusho) was applied to an iron plate (25 inches wide x 6 cm long), and an unvulcanized rubber sheet (7 mm thick) of each rubber composition produced as described above was placed on top of the cement to form a laminate, which was then press-vulcanized at 150°C for 30 minutes to bond the rubber composition to the iron plate, producing each sample. Each sample had a rubber layer and a metal layer.

[0076] (Peel test) For each sample prepared as described above, a peel test was performed in accordance with JIS K6256-2:2013 in which the rubber layer was peeled from each sample at an angle of 90° to the metal layer, and the peel strength (N / mm) was measured.

[0077] (Evaluation Criteria) In the present invention, when the peel strength exceeded 11.7 N / mm, the adhesion to iron (rubber-iron adhesion) was evaluated as excellent. On the other hand, when the peel strength was 11.7 N / mm or less, the adhesion to iron (rubber-iron adhesion) was evaluated as poor. The greater the peel strength is above 11.7 N / mm, the better the adhesion to iron (rubber-iron adhesion).

[0078] <Storage stability (heat aging resistance after storage of rubber composition)> Each rubber composition (unvulcanized) produced as described above was stored for one month under the condition of 25° C., and then an initially vulcanized rubber (thickness 2 mm) after storage was obtained in the same manner as for the initially vulcanized rubber described above. Using each initial vulcanized rubber after storage obtained as described above, samples were prepared in the same manner as in the above <Heat aging resistance (without storage of rubber composition)>, and tensile tests were performed to measure (TB after heat aging) [MPa] and elongation at break (EB after heat aging) [%] of each heat aging test piece after storage. The product of TB and EB measured as described above was calculated.

[0079] (Evaluation Criteria) In the present invention, when the value of the product of TB and EB calculated as above is 7200 or more, the rubber composition is evaluated as having excellent heat aging resistance after storage and excellent storage stability. On the other hand, when the value of the above product was less than 7200, the rubber composition was evaluated as having poor heat aging resistance after storage and poor storage stability. The larger the value of the product is than 7200, the better the heat aging resistance after storage of the rubber composition is, and the better the storage stability of the rubber composition is.

[0080] [Table 1]

[0081] [Table 2]

[0082] [Table 3]

[0083] Details of each component shown in Table 1 are as follows. (Rubber component) NR: Natural rubber, TSR20, manufactured by THAITECH RUBBER Co., Ltd. SBR: Nipol 1502, manufactured by Zeon Corporation BR: Product name Nipol BR 1220L, manufactured by Zeon Corporation

[0084] (Carbon Black) Carbon black 1 (N660): GPF grade carbon black, product name DASHBLACK, manufactured by OCI, N2SA25~30m 2 / g Carbon black 2 (N550): FEF grade carbon black, product name Asahi #60UG, manufactured by Asahi Carbon Co., Ltd., N2SA40~45m 2 / g

[0085] Silica: Product name: Nipsil VN3, manufactured by Tosoh Silica Corporation Silane coupling agent: Product name Si69, manufactured by Degussa Zinc oxide: Product name "Zinc oxide type 3", manufactured by Seido Chemical Industry Co., Ltd. Stearic acid: Product name "Lunac S-25", manufactured by Kao Corporation

[0086] Amine-based antioxidant (6PPD): N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (structure below), manufactured by Ouchi Shinko Chemical Industry Co., Ltd. [ka] Antioxidants other than amines: Phenol-based antioxidants. 2,6-di-tert-butyl-4-methylphenol, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0087] Vulcanization accelerator DM: Di-2-benzothiazolyl disulfide. Noccela DM-P, manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator CZ: Sancerer CM-PO, manufactured by Sanshin Chemical Industry Co., Ltd.

[0088] (Plasticizer) Paraffin oil: Product name: Machine oil, manufactured by Showa Shell Co., Ltd. According to ASTM D2140-08 (2017) (C A %4.5%, C P %65%, C N %30.5%) Aroma oil: A-OMIX, manufactured by Sankyo Yuka Kogyo Co., Ltd. C according to ASTM D2140-08 (2017) A %29%, C P %44%, C N %27%. A-OMIX is the C A Since the content is 25% or more, it corresponds to the specific aroma oil of the present invention.

[0089] Plasticizer 1: Product name: Refined Castor Oil-1, manufactured by Ito Oil Mills Co., Ltd.

[0090] Sulfur: Oil-treated sulfur (Hosoi Chemical Industry Co., Ltd.) Net sulfur content is 95% by mass

[0091] As is clear from the results shown in Table 1, Comparative Examples 1 to 4 in which the total content of at least the natural rubber and butadiene rubber did not satisfy the predetermined amount were poor in heat aging resistance and / or adhesion to iron. Comparative Example 5, in which the content of butadiene rubber exceeded the predetermined amount, had poor heat aging resistance. Comparative Example 6, which did not contain butadiene rubber, had poor heat aging resistance and adhesion to iron. Comparative Examples 7 and 8, which contained an amine-based antioxidant or a specific aromatic oil, had poor stain resistance. Comparative Example 9, in which the carbon black content was less than the specified amount, had poor heat aging resistance and poor adhesion to iron. Comparative Example 10, in which the carbon black content was greater than the prescribed amount, had poor heat aging resistance. Comparative Example 11, which did not contain carbon black but contained silica and a silane coupling agent instead, had poor adhesion to iron. Moreover, in Comparative Examples 1, 3 to 5, and 10, the heat aging resistance after storage of the rubber composition was reduced, and the storage stability of the rubber composition was poor.

[0092] In contrast, the rubber composition of the present invention is excellent in adhesion to iron, heat aging resistance and stain resistance. In addition, when the rubber composition of the present invention has a butadiene rubber content of less than 40 mass% in the total rubber component (Examples 2 to 13), the rubber composition has better heat aging resistance after storage and better storage stability than when the butadiene rubber content is 40 mass% (Example 1). In Examples 1 to 13, each of the initially vulcanized rubbers (thickness: 2 mm) produced as described above was black in color. [Explanation of symbols]

[0093] 100 Fender 102 Main unit 104, 106 Metal fittings A Part of main body 102 200 outer layer 202 Inner layer 204 Reinforcement layer

Claims

1. The rubber component contains natural rubber and butadiene rubber, and carbon black, The content of the butadiene rubber is 40 mass% or less in the total amount of the rubber component, a total content of the natural rubber and the butadiene rubber is 90 mass% or more of the total amount of the rubber component, The amount of the carbon black is 30 to 60 parts by mass based on 100 parts by mass of the rubber component, C obtained by composition analysis using the Kurtz method A It does not substantially contain aromatic oils with a content of 25% or more, A rubber composition for a fender, which is substantially free of an amine-based antioxidant.

2. The rubber composition for a fender according to claim 1, further comprising a plasticizer (excluding the aromatic oil), the plasticizer including paraffin oil.

3. The rubber composition for fenders according to claim 2, wherein the content of the plasticizer is 5 to 20 parts by mass based on 100 parts by mass of the rubber component.

4. The rubber composition for a fender according to any one of claims 1 to 3, wherein the content of the carbon black is 40 to 59 parts by mass based on 100 parts by mass of the rubber component.

5. The rubber composition for a fender according to any one of claims 1 to 4, wherein the rubber component is substantially free of styrene-butadiene rubber.

6. The rubber composition for a fender according to any one of claims 1 to 5, wherein the rubber component contains only natural rubber and butadiene rubber.

7. It also contains sulfur, The rubber composition for a fender according to any one of claims 1 to 6, wherein the content of the sulfur is 1.7 to 2.2 parts by mass based on 100 parts by mass of the rubber component.

8. The rubber composition for a fender according to any one of claims 1 to 7, further comprising a vulcanization accelerator, the vulcanization accelerator including a thiazole-based vulcanization accelerator.

9. A fender formed using the rubber composition for a fender according to any one of claims 1 to 8.

10. An outer layer and an inner layer are provided, and a reinforcing layer is provided between the outer layer and the inner layer, and the reinforcing layer has a reinforcing material and a coating layer, The fender according to claim 9 , wherein either or both of the inner layer and the coating layer are each independently formed using the rubber composition for a fender.

11. The fender according to claim 9 or 10, which has an appearance color of white or color.

Citation Information

Patent Citations

  • Rubber composition for fender and fender

    JP2008179656A

  • Rubber composition for fender cover layer and fender material using the same

    JP2013194155A

  • Rubber composition

    JP2014098102A

  • Rubber composition for fender, and fender

    JP2015218185A

  • Rubber composition and vulcanized rubber

    JP2019044137A